2021
DOI: 10.3389/fmicb.2021.692515
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL23 Attenuates Signal Transducer and Activator of Transcription 1 Phosphorylation and Type I Interferon Response

Abstract: Human cytomegalovirus (HCMV), the human beta-herpesvirus, can cause severe syndromes among both immunocompromised adult patients and newborns. Type I interferon (IFN-I) exerts an important effect to resist infections caused by viruses such as HCMV, while IFN evasion may serve as a key determining factor for viral dissemination and disease occurrence within hosts. In this study, UL23, a tegument protein of HCMV, was confirmed to be a key factor for negatively regulating the type I IFN immune response. A detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We have demonstrated that pA104R inhibited ISGF3-mediated ISRE luciferase signaling (Figure 2A), suggesting that pA104R is a suppressor of IFN signaling that likely targets ISGF3 itself or a related downstream process. Previous studies have shown that many viral proteins can subvert the IFN-I signaling pathway by targeting IRF9 or STATs to reduce phosphorylation or stimulate degradation (Palosaari et al, 2003;Fanunza et al, 2021;Feng et al, 2021). Further studies revealed that although pA104R did not interact with any component of ISGF3 (Figure 3), it still attenuated the phosphorylation of STAT1 (Figure 2B).…”
Section: Discussionmentioning
confidence: 87%
“…We have demonstrated that pA104R inhibited ISGF3-mediated ISRE luciferase signaling (Figure 2A), suggesting that pA104R is a suppressor of IFN signaling that likely targets ISGF3 itself or a related downstream process. Previous studies have shown that many viral proteins can subvert the IFN-I signaling pathway by targeting IRF9 or STATs to reduce phosphorylation or stimulate degradation (Palosaari et al, 2003;Fanunza et al, 2021;Feng et al, 2021). Further studies revealed that although pA104R did not interact with any component of ISGF3 (Figure 3), it still attenuated the phosphorylation of STAT1 (Figure 2B).…”
Section: Discussionmentioning
confidence: 87%
“…Their translation happens in three post‐infection stages: IE, early (E), and late (L), which interact with physiological cellular activities 3 . CMV‐infected cell activates the STAT1/2/3 axis through many mechanisms such as US28, 161 IL6, Platelet‐derivedgrowth factor receptor (PDGFR), 158 IFN‐ß, 162 UL23, 163 IL10 164‐167 (Figure 5).…”
Section: Data Extractionmentioning
confidence: 99%
“…Ul23, a tegument protein of HCMV, can significantly decrease the expression of ISGs and the activity of the promoter of the response elements of ISGs during HCMV infection. UL23 is a key factor in the negative regulation of type I IFN-mediated immune responses ( 71 ). HCMV inhibits the cGAS-STING-TBK1 pathway and decreases IFN-β mRNA accumulation via its latent associated protein UL138 ( 72 ).…”
Section: Cgas-sting Pathway and Hhv Infectionsmentioning
confidence: 99%